SPAWNING FREQUENCIES AND BREEDING SEASONS OF SOME FRESHWATER FISHES WITH SPECIAL REFERENCE TO THOSE OCCURRING IN THE PLAINS OF NORTHERN INDIA - Qasim, S Z; Qayyum, A (Indian Journal of Fisheries, 2011)
IT is well known that the differences in the spawning behaviour of teleostscan to a certain extent be illustrated on the basis of the condition revealedby the unspawned eggs in the ovary (Heidrich, 1925; Clark, 1925, 1934;Hickling and Rutenberg, 1936). Many studies on the ova diameter frequencieshave been undertaken during recent years and in almost all casesit has been accepted that species which have all the ovarian eggs of similarsize spawn them together whereas those which have a wide range in oocytesizes may have several groups of eggs matured and shed periodically duringthe breeding season (De Jong, 1939; Prabhu, 1956 and Dharmamba, 1959).Qasim (1956 a and 1956 b) made similar studies on two marine fishes Blenniuspholis L. and Centronotus gunnellus (L.) and confirmed his results on thefrequency of spawning by an observation in the aquarium.